Poverty statistics of South Sulawesi Province based on Human Development Index and GRDP using panel data - Iwan Harsono; Fajri Hatim; Efriyani Sumastuti; Bahrun Thalib; Ridwan Sya’rani (International Journal on Social Science, Economics and Art, 2024)
This study examines the impact of Human Development Index (HDI) and Gross Regional Domestic Product (GRDP) on poverty in South Sulawesi Province using quantitative methods with multiple regression analysis techniques and panel data from 24 Districts/Cities. Results from SPSS version 26 indicate that HDI insignificantly affects poverty (p = 0.413, t = 0.821, β = 1.523), while GRDP significantly influences poverty (p = 0.000, t = 5.441, β = 0.978). These findings suggest that policymakers should consider GRDP growth to alleviate poverty, rather than relying solely on HDI. This research provides valuable insights for the South Sulawesi government to address poverty based on income levels, as reported by the South Sulawesi Central Bureau of Statistics, and to monitor HDI and GRDP trends annually.